Intratumoral CCR5+ neutrophils identify immunogenic subtype muscle-invasive bladder cancer with favorable prognosis and therapeutic responses. (1st January 2020) - Xiang, Zhuoyi; Zhou, Quan; Zeng, Han; Wang, Zewei; Zhang, Hongyu; Liu, Zhaopei; Huang, Qiuren; Chang, Yuan; Bai, Qi; Xia, Yu; Wang, Yiwei; Liu, Li; et al.
ABSTRACT: Our previous studies revealed tumor-infiltrating neutrophils (TINs) played dichotomous roles in different cancers, indicating diverse TINs subtypes might orchestrate anti-tumor immunity or immune evasion, respectively. This study aimed to investigate the clinical significance and immune characteristics of CCR5 + TINs in muscle-invasive bladder cancer (MIBC). Two hundred and fifty-seven MIBC patients from two clinical centers and 95 fresh MIBC samples were included. CCR5 + TINs were stained by immunohistochemistry, and the relationship between patients' clinic-pathological features and prognosis was evaluated, respectively. Immunohistochemistry and flow cytometry were applied to assess the immune features of CCR5 + TINs and their correlations with other immune cells. In vitro study was conducted to estimate immune characteristics of CCR5 + TINs and their predictive potential for pembrolizumab therapeutic response. In the two MIBC cohorts, we found that high CCR5 + TINs infiltration could predict better overall survival (OS, P = .032, 0.039) and recurrence-free survival (RFS, P = .001, 0.006) and be associated with survival benefit from adjuvant chemotherapy (ACT, P < .001 for OS and P = .022 for RFS, respectively) in merely pT2N0 MIBC. Maraviroc could partly reduce IFN-γ secretion by CCR5 + TINs ( P < .001). CCR5 + TINs correlated with higher expression of effector molecules within CD8 + T cells. Notably, pembrolizumab treatment could only elevate the apoptosis status of tumor cells in the CCR5 + TINs high subgroup ( P <  .001), other than CCR5 + TINs low subgroup ( P = .481). Our results indicate that CCR5 + TINs could prime anti-tumor immune response through autonomous IFN-γ release, thus leading to favorable prognosis and superior therapeutic response to ACT and immunotherapy in MIBC.